A Comment on James M. Poterba's ‘Demographic Structure and Asset Returns’ - Campbell, John Y. (The Review of Economics and Statistics, 2001)
November 01 2001 A Comment on James M. Poterba's ‘Demographic Structure and Asset Returns’ John Y. Campbell John Y. Campbell Harvard University Search for other works by this author on: This Site Google Scholar Author and Article Information John Y. Campbell Harvard University Received: June 12 2001 Accepted: June 12 2001 Online ISSN: 1530-9142 Print ISSN: 0034-6535 © 2001 President and Fellows of Harvard College and the Massachusetts Institute of Technology2001 The Review of Economics and Statistics (2001) 83 (4): 585–588. https://doi.org/10.1162/003465301753237669 Article history Received: June 12 2001 Accepted: June 12 2001 Cite Icon Cite Permissions Share Icon Share Facebook Twitter LinkedIn Email Views Icon Views Article contents Figures & tables Video Audio Supplementary Data Peer Review Search Site Citation John Y. Campbell; A Comment on James M. Poterba's ‘Demographic Structure and Asset Returns’. The Review of Economics and Statistics 2001; 83 (4): 585–588. doi: https://doi.org/10.1162/003465301753237669 Download citation file: Ris (Zotero) Reference Manager EasyBib Bookends Mendeley Papers EndNote RefWorks BibTex toolbar search Search Dropdown Menu toolbar search search input Search input auto suggest filter your search All ContentAll JournalsThe Review of Economics and Statistics Search Advanced Search This content is only available as a PDF. © 2001 President and Fellows of Harvard College and the Massachusetts Institute of Technology2001 Article PDF first page preview Close Modal You do not currently have access to this content.